Medicine or caring science in Ancient Greece - Pilar Darriba Rodríguez (Universidad de Alicante, 1999)
Looking back in history we could trace the onset of so called medicine or caring science, together with the onset of nursing. Returning to Greece and its classical period (3rd or 5th century B.C) or Pericles's century, we could observe they used the original words to those we use nowadays in the health sciences. Some of those words are even exactly the same. The present study explores mythology, medicine and nursing in classical Greece, in order to evaluate its origin and meaning, and proving that those sciences have developed from the beginning of mankind to the present time. As has been said over and again: a collective who knows its origins could better evaluate its present, and participate in its further development in a more effective way.